Energy transitions in Central and Eastern Europe : the political economy of climate and energy policy / Tomas Maltby, King's College London, Matúš Mišík, Comenius University in Bratislava. - Maltby, Tomas; Mišík, Matúš, 1984- (Cambridge studies on environment, energy and natural resource governance., 2024)
This book examines the mutual interplay of climate and energy policies in eleven Central and Eastern European countries in the context of the EU's energy transition. Energy security has long been prioritised in the region and has shaped not only national climate and energy policy, but also EU-level policy-making and implementation. Whilst the region shares economic, institutional and historical energy supplier commonalities it is not homogenous, and the book considers the significant differences between the preferences and policies of these member states. Chapters also explore the effect of the EU on member states that have joined since 2004 and their influence on the EU's energy and climate policies and their role in highlighting the importance of the concepts of security and solidarity. The book highlights the challenges to, and drivers of, energy transitions in the region and compares these with those in global energy transitions.